PENGELOLAAN KELAS DAN PENERAPANNYA DALAM PEMBELAJARAN BAHASA ARAB - Nuryani, Nuryani (Jurnal Bahasa Lingua Scientia, 2012)
In the process of teaching Arabic, a teacher may not neglect the classroom management. Classroom management is an effort to utilize the class potential optimally to achieve the learning objectives. The classroom management is badly needed since from time to time, the attitude and the behavior of the learner changes. Therefore, class is always dynamic in term of the attitude, behavior, mental, and emotional changing of the students.